1997
DOI: 10.1128/jvi.71.12.9466-9474.1997
|View full text |Cite
|
Sign up to set email alerts
|

Increased probability of expression from modified retroviral vectors in embryonal stem cells and embryonal carcinoma cells

Abstract: Gene expression from the Moloney murine leukemia retrovirus (Mo-MuLV) is highly restricted in embryonic carcinoma (EC) and embryonic stem (ES) cells. We compared levels of expression in PA317 fibroblasts, F9 (EC) cells, and CCE (ES) cells by Mo-MuLV-based vectors and vectors based on our previously reported MND backbone, which has alterations to address three viral elements implicated as repressors of expression byMo-MuLV: the enhancer, the primer binding site, and the negative-control region. Expression was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 52 publications
2
33
1
1
Order By: Relevance
“…E14 and CCE ESC lines are derived from 129/SV mouse embryos [25,26]. E14 and CCE ESC lines were cultured on gelatinized plates in Dulbecco's modified Eagle's medium (DMEM) with 15% ESC-qualified fetal calf serum (FCS; HyClone, Logan, UT, http://www.hyclone.com), 5.5 × 10 −2 mM ÎČ-mercaptoethanol (Gibco BRL, Carlsbad, CA, http://www.gibcobrl.com), and 10 3 U/ml leukemia inhibitory factor (LIF) (ESGRO; Chemicon International, Temecula, CA, http://www.chemicon.com).…”
Section: Cell Culture and Embryoid Body Formationmentioning
confidence: 99%
“…E14 and CCE ESC lines are derived from 129/SV mouse embryos [25,26]. E14 and CCE ESC lines were cultured on gelatinized plates in Dulbecco's modified Eagle's medium (DMEM) with 15% ESC-qualified fetal calf serum (FCS; HyClone, Logan, UT, http://www.hyclone.com), 5.5 × 10 −2 mM ÎČ-mercaptoethanol (Gibco BRL, Carlsbad, CA, http://www.gibcobrl.com), and 10 3 U/ml leukemia inhibitory factor (LIF) (ESGRO; Chemicon International, Temecula, CA, http://www.chemicon.com).…”
Section: Cell Culture and Embryoid Body Formationmentioning
confidence: 99%
“…E14, CCE, and RI are ES cell lines derived from 0129 mouse embryos [10,11]. ES cell lines were cultured on gelatinized plates in Dulbecco's modified Eagle's medium (DMEM) with…”
Section: Cell Culture and Condition Mediamentioning
confidence: 99%
“…vector constructs and packaging cell lines. As a retroviral vector, GCDNsap described here is constructed similarly to MND vector developed by Kohn's group which has the dl587rev derived primer binding site and the NCR devoid LTR whereas GCDNsap is different from MND in the virus LTR and backbone; the former is a spliced-type retroviral vector with the PCMV LTR and the latter is a LN type vector with the MPSV LTR (Robbins et al 1997). Consistent with the results obtained from the present study, MND also showed high and continued expression of the transgene in immature cells such as EC and ES cells as well as murine hematopoietic stem cells (Halene et al 1999).…”
Section: Discussionmentioning
confidence: 99%